Studies of high energy density physics and laboratory astrophysics driven by intense lasers. (May 2016) - Zhang, J; Li, Y T; Chen, L M; Dong, Q L; Zhong, J Y; Wang, W M; Sheng, Z M; Zhao, G
Abstract: Laser plasmas are capable of creating unique physical conditions with extreme high energy density, which are not only closely relevant to inertial fusion energy studies, but also to laboratory simulation of some astrophysical processes. In this paper, we highlight some recent progress made by our research teams. The first part is about directional hot electron beam generation and transport for fast ignition of inertial confinement fusion, as well as a new scheme of fast ignition by use of a strong external DC magnetic field. The second part concerns laboratory modeling of some astrophysical phenomena, including 1) studies of the topological structure of magnetic reconnection/annihilation that relates closely to geomagnetic substorms, loop-top X-ray source and mass ejection in solar flares, and 2) magnetic field generation and evolution in collisionless shock formation.